ANALISIS DAN PERENCANAAN SISTEM DRAINASE JALAN PELITA 1 KECAMATAN MEDAN PERJUANGAN KOTA MEDAN - Saragi, Tiurma Elita; Saragi, Yetty Riris; Zai, Eben Oktavianus; Harefa, Masati (Jurnal Visi Eksakta, 2021)
The occurrence of flooding on Jln.Pelita 1, Medan Perjuangan District in Medan City was caused by the inability of the existing drainage channel to accommodate direct runoff and blockage of drainage channels by garbage.The hydrological analysis uses maximum rainfall data for the last 10 years, then calculations are carried out that aim to calculate the planned discharge using the rational method. The area of ​​the Medan Perjuangan sub-district is 0.2475 Km2 with hydraulics analysis carried out to calculate the discharge capacity of the drainage channel using the Continuity formula and the Manning formula, after which the appropriate system and dimensions are planned. With a ketchment area of ​​Medan Perjuangan sub-district 0.2475 km2, the calculation of drainage planning using the Gumbel Method of planned rainfall for a return period of ±10 years, with the largest discharge on the combined section of the primary canal and the Kemiling area. Then it was found that the flood height in the research area was as high as 10-20 cm and because of the existing dimensions it was not able to accommodate the design discharge. Thus, the appropriate channel dimensions are planned using a shaped cross section so that the design discharge (Qr) > channel discharge (Qs).